Molecular Identification of Aspergillus fumigatus Using ISSR and RAPD Markers - Kadhim Rassin, Nawras; Al- judy, Neamat J.; Imran Dheeb, Batol (Iraqi Journal of Science, 2023)
The aim of this stud to isolate and identified of A. fumigatus from different sources and study the genetic diversity among these isolates by using RAPD and ISSR markers.Collected 20 samples from 7samples were isolated A. fumigatusisolates were characterized depending on its morphological, then extracted DNA from its.RAPD markersrandomly bandingwith sitesof genome more than ISSR markers where the primer OPN-07 achieved discriminative power (19.1) and 43 bands, while ISSR6 achieved discriminative power (17.1) with 32 bands.ISSR were more efficiency in specific binding then RAPD, ISSR primers has great a binding to production unique band, when 9 primers from 01 primers, ISSR9 was produce (5) unique bands, while RAPD markers was low ability to production unique bands, 3primers from 9 primers were produced unique bands.The dendrogram of RAPD was reverted than isolates number 5 and 7 had the great genetic diversity 0.33361 while the isolates number 5 and 6 had the lowest genetic similarity 0.98521 in contrast with ISSR markers was show isolates number1 and 2 greats genetic diversity 0.97826whilethe isolates number 5 and 7 had the lowest genetic similarity 0.10253.